Faktor yang Berhubungan dengan Kejadian Dermatitis Kontak pada Penambang Pasir di Sungai Citanduy Kabupaten Cilacap - Rizal Maulana Firdaus; Nur Isnaeni; Isna Hikmawati; Meida Laely Ramdani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Contact dermatitis is a common inflammatory skin condition caused by exposure to irritants and allergens. The occupational type is the most frequent form, often affecting the hands and face due to direct exposure. This study aimed to identify factors associated with the occurrence of contact dermatitis among sand miners working in the Citanduy River, Cilacap Regency. Using a case-control design, data were collected from 60 sand miners selected through purposive sampling, a non-probability technique based on the researcher’s knowledge of the population.The findings showed that work duration had no significant relationship with contact dermatitis (P=0.127; OR=3.250). Personal hygiene was significantly associated with the condition (P=0.00; OR=16.429), indicating that poor hygiene greatly increases risk. The use of personal protective equipment (PPE) was not significantly related (P=0.19; OR=4.125). Occupational history showed a strong and significant association (P=0.00; OR=17.376), suggesting that previous job exposure contributes to dermatitis. No significant relationship was found between allergy history and contact dermatitis (P=0.333; OR=2.364). Meanwhile, a history of skin disease was significantly associated (P=0.002; OR=6.909), meaning workers with prior skin problems were more vulnerable.In conclusion, work duration, PPE use, and allergy history were not significantly associated with contact dermatitis. However, personal hygiene, occupational history, and previous skin disease were key contributing factors. These findings emphasize the importance of improving hygiene and monitoring workers with a history of skin conditions to reduce the risk of contact dermatitis among sand miners.